(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Because of the importance of maintaining track of all products in one location, barcodes have become important elements of sales and product services. Many methods have been developed to make the task of reading barcodes more user-friendly. This project aims to use image processing as a technique for recognizing the barcode using the camera. Using this technique, the machines will be able to read the barcode using the camera and can decode the information on the barcode using the software capable of image processing [1]. The platform will be created for the MATLAB software package and will function with a webcam or digital camera as an interface. On the Graphical User Interface, the device can analyse the image and display the barcode type, data, and image size (GUI) [1]. The machine is designed to identify different types of barcodes and display the data if the barcode image is obtained. The machine is also intended to provide a more convenient and cost-effective way of viewing data from barcodes than electronic barcode scanners. An individual who wants to inspect data identified by barcode numbers without having to go to a location that provides barcode scanner services can use this computer at any time and from any location [1]. As a result, the project has gone smoothly and without a hitch. It is advised that the computer have a slider so that the user can change the brightness of the image captured by the webcam for future device enhancement.